Postmenopausal Meigs' Syndrome in Elevated CA-125: A Case Report - Park, Jung-Woo (J Menopausal Med, 2015)
Meigs' syndrome is a benign ovarian tumor associated with ascites and pleural effusion. Elevated cancer antigen 125 (CA-125) in Meigs' syndrome is an unusual clinical condition reported in few cases. We report here on a 61-year-old woman who presented with dyspnea; in imaging assessment, a heterogeneous pelvic mass measuring 12 × 11 cm with ascitic fluid was reported. Pleural effusion was detected on Chest X-ray. Aspiration of pleural fluid showed no evidence of malignancy. CA-125 level was 347 IU/mL. The patient underwent laparotomy during which a mass measuring 12 × 11 cm was detected in her left adnexa. Histology showed ovarian thecoma. The mass was resected, and, after that, the symptoms disappeared and CA-125 level reached 19 IU/mL. The patient had experienced no problem after 12 months of follow up. Although postmenopausal women with ovarian tumor, ascites, pleural effusion, and elevation of CA-125 levels probably have malignant ovarian tumors, Meigs' syndrome must be considered in the differential diagnosis.